The Effect of Waves on the Maneuvering Characteristics of Ferry Vessel - Mansyur Hasbullah; Daeng Paroka; Hanisa Hanisa (Jurnal Penelitian Enjiniring, 2017)
Wave is one of the natural phenomena that give effect to the cruise ship. The energy produced by the wave is very large that makes the ship turn directions. Therefore the turn has an error coordinates of starting point of ship. Deviation of the coordinates has made ​​a farther distance and increase of fuel consumption, so the operational costs being higher. In the research would predict the drift angle, the ship speed and large of rudder angle to be used after the ship got the influence of wave. Taking into account the motion of surge, sway, yaw. Simulations performed by using Delphi software, with variations of the height of wind Hw = 0,5 m, 1 m, 1,5 m and 2 m, flatness of the wave = 0,01, the speed of the wind ratio Uw/U= 0 – 20 m/s and wave direction coaming ψw = 0º - 180º on the side of the ship . Obtained that the biggest of drift angle happened on 50º wave direction. The biggest of rudder angle happened on 110º wave direction while that ship speed happened on 160º wave direction.